The Influence of leadership styles on the performance of NGOs in the health sector in Nairobi County, Kenya - Otieno, Maureen Atieno (Strathmore University, 2022)
Non-governmental organizations play a critical role in the community, especially in the health sector, as most of the research conducted comes from donor funding. Leadership is not the main area of focus in NGOs as there are other life-threatening and other issues to focus on. However, with continuous collaboration and interconnectivity within institutions, there is a dire need to hold leaders accountable for their actions. The purpose of this study was to establish the influence of leadership styles on the organizational performance of NGOs in the health sector in Nairobi County, Kenya. The specific objective included determining the influence of transactional, transformational, and democratic leadership styles on the organizational performance of NGOs in the Health sector in Nairobi County in Kenya. The study was anchored on Stewardship theory and style and behavior theory. A descriptive survey was adopted. The study population consisted of 240 top management team in the health sector NGOs in Nairobi County. The top management team comprised of Country managers; the Chief Executive Officer or Executive Director; the Project Manager or Director; and the Grants Manager or Director. A questionnaire patterned after Multifactor Leadership Questionnaire was used to collect data that was analyzed using SPSS software (SPSS Version 26.0) and the result was presented in tabular form. According to the research findings using descriptive research design, leadership style influences organizational performance but the most influential leadership style was transformational leadership. There were traces of democratic leadership style in the health sector NGOs. The findings also indicated a positive correlation between variables explored in the study. The variation in organizational performance due to transactional, transformational, and democratic leadership was minimal compared to other factors in the health NGO sector. Majority of the leaders in the health sector NGOs were highly educated young professionals. This study was limited to Nairobi County Health Sector NGOs. A further look into the other counties is recommended. The employees indicated that organizational performance was influenced by other factors such as appraisals, goal setting, periodic reviews, employee incentives, knowledge, and skills, change management and innovation and organization culture. A relook into the suggested factors can bring insight into how these factors affect the health sector NGOs. The study was limited to the three-leadership style and recommends that other leadership styles in the health sector NGOs be explored. The study concluded that in general transactional, transformational and democratic leadership style gave organizations a competitive edge that influenced organizational performance positively.
A Thesis submitted in partial fulfillment of the requirements for the award of degree of Master of Commerce at Strathmore University